2021
DOI: 10.1038/s41419-021-03577-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of eIF5A hypusination reprogrammes metabolism and glucose handling in mouse kidney

Abstract: Inhibition of the eukaryotic initiation factor 5A activation by the spermidine analogue GC7 has been shown to protect proximal cells and whole kidneys against an acute episode of ischaemia. The highlighted mechanism involves a metabolic switch from oxidative phosphorylation toward glycolysis allowing cells to be transiently independent of oxygen supply. Here we show that GC7 decreases protein expression of the renal GLUT1 glucose transporter leading to a decrease in transcellular glucose flux. At the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…They observed a decrease in the protein content of complexes II and V and an increase in complex III, in parallel with a metabolic shift from oxidative to glycolytic metabolism. The same result has also been obtained in renal cells treated with GC7 that impaired eIF5A hypusination of both isoforms [ 78 , 79 ]. However, cells treated with siVA show a significant increase in respiration coupled to oxidative phosphorylation.…”
Section: Apoptosis and Mitochondriasupporting
confidence: 73%
See 4 more Smart Citations
“…They observed a decrease in the protein content of complexes II and V and an increase in complex III, in parallel with a metabolic shift from oxidative to glycolytic metabolism. The same result has also been obtained in renal cells treated with GC7 that impaired eIF5A hypusination of both isoforms [ 78 , 79 ]. However, cells treated with siVA show a significant increase in respiration coupled to oxidative phosphorylation.…”
Section: Apoptosis and Mitochondriasupporting
confidence: 73%
“…It is known that a deficiency in dhps or chronic treatment with DHPS inhibitors, like GC7, enhances glucose tolerance and glycemia in different mouse models of diabetes (HFD [ 72 , 73 ], STZ [ 48 , 74 ] humanized mouse model of T1D [ 75 ], db/db [ 76 ], NOD [ 77 ]). Searching for the impact of GC7 mediated eIF5A inhibition on renal glucose metabolism, Cougnon et al [ 78 ] reported that GC7 decreased protein expression of the renal GLUT1 glucose transporter in cultured proximal cells resulting in a decrease in trans-cellular glucose flux. In parallel, GC7 modified the native energy supply of the proximal cells from glutamine toward glucose use.…”
Section: Metabolismmentioning
confidence: 99%
See 3 more Smart Citations